Avaliação da pressão liquórica em pacientes obstétricas submetidas à anestesia subaracnoidea que apresentaram cefaleia pós-punção dural - Pimentel, Ivandete Coelho Pereira [UNESP] (2014)
Introduction: Subarachnoid anesthesia is the choice technique for c-section surgery. Postdural puncture headache is a complication of the technique and occurs especially in women less than 40 years of age. Possible mechanisms involved in the origin of the headache are líquoric hypothension due to loss of cerebrospinal fluid through the puncture hole of the dura mater and arachnoid leading to the stretch of the intracranial structures and compensatory dilation of the veins. Postdural puncture headache may have self-limited evolution or results in complications like subdural hematoma, cerebral venous thrombosis and death. Objective: Evaluate liquoric pressure of pregnant women submitted to c-section surgery at the time of anesthesia e during the headache. Correlate the headache with the characteristics of the patients and the anesthetic technique. Methods: After approval of the ethic committee and signature of the informed consent, 721 pregnant women submitted to c-section surgery who were also submitted to subarachnoid anesthesia were enrolled in this prospective study, with standardized technique, between January 2012 and May 2013. Liquoric pressure was evaluated in the moment of anesthesia in all the patients and, in the moment of diagnosis, in the patients who presented headache. For this, was used a pressure manometer of aneroid type. The pregnant women were evaluated for body mass index (BMI), physical state (ASA), pre-operatory diagnosis and diseases that occurred during the pregnancy, subarachnoid space approach, inter-vertebral space and number of spaces that were punctured, number of puncture tries, presence of adjuvant drugs and their type. The patients were evaluated in terms of presence of postdural puncture headache, 12 hours, 24 hours, 48 hours and 72 hours after the realization of subarachnoid puncture. For statistical analysis, were realized the chi-square test, Pearson test, t-Studen test and variance ...